Age-Dependent Variations in Functional Quality and Proteomic Characteristics of Canine (Canis lupus familiaris) Epididymal Spermatozoa - Anna Zmudzinska; Jerzy Wisniewski; Piotr Mlynarz; Beata Olejnik; Marzena Mogielnicka-Brzozowska (International Journal of Molecular Sciences, 2022)
Increased male age is associated with a significant reduction in semen quality. Little is known about the sperm proteome changes resulting from the aging process. This study aimed to investigate the relationship between the functional quality and proteome of epididymal spermatozoa of dogs that were differing in age. The study was conducted on 30 male dogs that were divided into three age groups. G1—12 to 41 months old, G2—42 to 77 months old, and G3—78 to 132 months old. The sperm samples were assessed using a computer-assisted semen analysis (CASA). The epididymal sperm proteins were analyzed using gel electrophoresis (SDS-PAGE), nano-liquid chromatography coupled to quadrupole time of flight mass spectrometry (NanoUPLC-Q-TOF/MS) and bioinformatic tools. The sperm quality parameters were significantly lower in older dogs. NanoUPLC-Q-TOF/MS identification resulted in 865 proteins that were found in the G1, 472 in G2, and 435 in G3. There were seven proteins that were present in all three age groups, and four of them (ACTB, CE10, NPC2, CRISP2) showed significant changes among the studied groups. Age-dependent variations were detected in the sperm proteome composition and were related to important metabolite pathways, which might suggest that several proteins are implicated in sperm maturation and could be potential aging biomarkers.